1996
DOI: 10.1093/nar/24.9.1727
|View full text |Cite
|
Sign up to set email alerts
|

A 39 Amino Acid Fragment of the Cell Cycle Regulator p21 Is Sufficient to Bind PCNA and Partially Inhibit DNA Replication in vivo

Abstract: The cell cycle regulator p21 interacts with and inhibits the DNA replication and repair factor proliferating cell nuclear antigen (PCNA). We have defined a 39 amino acid fragment of p21 which is sufficient to bind PCNA with high affinity (Kd 10-20 nM). This peptide can inhibit DNA replication in vitro and microinjection of a GST fusion protein containing this domain inhibited S phase in vivo. Despite its high affinity for PCNA, the free 39 amino acid peptide does not have a well-defined structure, as judged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 39 publications
9
83
0
Order By: Relevance
“…Only the small and disordered p21 protein might have an affinity high enough to displace any other ligand from PCNA, explaining its dominant inhibition of DNA replication and cell cycle progression 31 . For instance, a C-terminal p21 fragment 32 binds PCNA with two orders of magnitude higher affinity than p15. Conversely, the affinity of PCNA for p15 is higher than for a PIPbox fragment of the p66 subunit of the replicative polymerase d (Pold; K d ¼ 15.4 mM, measured by ITC at 30°C) 29 , and similar to the translesion synthesis polymerase Z (TLS PolZ; K d ¼ 0.4 mM, measured by surface plasmon resonance at 25°C) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Only the small and disordered p21 protein might have an affinity high enough to displace any other ligand from PCNA, explaining its dominant inhibition of DNA replication and cell cycle progression 31 . For instance, a C-terminal p21 fragment 32 binds PCNA with two orders of magnitude higher affinity than p15. Conversely, the affinity of PCNA for p15 is higher than for a PIPbox fragment of the p66 subunit of the replicative polymerase d (Pold; K d ¼ 15.4 mM, measured by ITC at 30°C) 29 , and similar to the translesion synthesis polymerase Z (TLS PolZ; K d ¼ 0.4 mM, measured by surface plasmon resonance at 25°C) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A yeast two-hybrid screen identified PCNA as the cellular ligand for the DQ65-79 peptide, and this interaction was further confirmed by in vitro biochemistry and electron microscopy. Synthetic peptides derived from p21 interact with PCNA to block replication in vitro but have no effect on DNA synthesis in intact cells (12), most likely because they are not able to penetrate the cell membrane. In contrast, the DQ peptide interacts with PCNA in T cell nuclei when added to cells in culture and is highly anti-proliferative (6).…”
Section: Discussionmentioning
confidence: 99%
“…12 and this study; circular dichroism data not shown), while the DQ peptide has a strongly ␣ helical profile (data not shown). In addition, although both peptides can interact with PCNA, their mechanisms of inhibitory action are different as the p21 peptide binds to PCNA to block pol ␦-dependent replication (7,12) while the DQ65-79 peptide does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, through its carboxyl terminus, p21 is able to associate with proliferating cell nuclear antigen (PCNA) and inhibits the interaction of PCNA with replication factor (8), DNA polymerase ␦ (9, 10), and FEN1 (11,12), leading to inhibition of DNA synthesis (13,14).…”
mentioning
confidence: 99%